A Systematic Review and Meta-analysis of Injecting Drug Use as a Risk Factor of HIV in Bangladesh (Dhaka University Journal of Science, 2023)
HIV is a new, transpiring problem, especially, among injecting drug users (IDU) in Bangladesh. Although HIV prevalence in Bangladesh compared to the neighboring countries is still low, ongoing high-risk behaviors among injecting drug users could facilitate the more extensive transmission of HIV to the general population. This study aims to assess the relationship between HIV and injecting drug use. Through a systematic review, we included 19 studies that met the inclusion/exclusion criteria. Pooled prevalence, odds ratio, 95% CI, and measures of heterogeneity were calculated by the random-effects model. Publication bias was examined by funnel plots and Egger‘s test. We found the overall pooled prevalence was 3.65% (95% CI: 2.10-5.56%) which indicates that Bangladesh is on the brink of a concentrated epidemic. IDUs were 6.085 times more likely to be HIV-positive than non-IDUs (pooled OR: 6.085; 95% CI: 4.654-7.956). The pooled prevalence for males was reported to be 2.44% (95% CI: 1.51-3.57%), which was significantly higher than those for females with a pooled prevalence of 0.26% (95% CI: 0.00-1.19%). This meta-analysis revealed that injecting drug use is a significant risk factor for HIV in Bangladesh. Moreover, while the HIV prevalence in female IDUs was found to be very low, it was much higher in male IDUs.Dhaka Univ. J. Sci. 71(2): 160-168, 2023 (July)